2019
DOI: 10.3390/ijms20235914
|View full text |Cite
|
Sign up to set email alerts
|

Emetine Synergizes with Cisplatin to Enhance Anti-Cancer Efficacy against Lung Cancer Cells

Abstract: Cisplatin is still the primary therapeutic choice for advanced lung cancers without driver mutations. The occurrence of cisplatin resistance is a major clinical problem in lung cancer treatment. The natural extracted agent emetine reportedly has anticancer effects. This study aimed to explore the possible role of emetine in cisplatin resistance. We used cell viability, Western blot, and Wnt reporter assays to show that emetine suppresses proliferation, β-catenin expression, and Wnt/β-catenin signaling in non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
1
12
0
2
Order By: Relevance
“… 72 Emetine can treat lung cancer in cooperation with cisplatin. 73 The roles of aminoglutethimide and emetine in the treatment of UCEC still need further analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 72 Emetine can treat lung cancer in cooperation with cisplatin. 73 The roles of aminoglutethimide and emetine in the treatment of UCEC still need further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that emetine exhibited antitumor effects in various cancers through various pathways. For example, emetine sensitizes ovarian and bladder cancer cells to cisplatin [ 12 , 13 ], and emetine exhibits anticancer activity in breast cancer and non-small cell lung cancer (NSCLC) cells [ 14 , 15 ]. In addition, emetine can decrease contracting Zika and Ebola viruses by suppressing the replication and invasion of viruses [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…They were obtained from Professor Yi-Ching Wang (National Cheng Kung University, Taiwan). We cultured cells in Roswell Park Memorial Institute ( RPMI) 1640 medium (Gibco, Gaithersburg, MD, USA) supplemented with 10% heat-inactivated fetal bovine serum (FBS) and other components as previously described [ 77 ]. All cell cultures were maintained in an incubator containing 5% CO 2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%